STUDI KASUS: ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. S UMUR 24 TAHUN DI PUSKESMAS KEPIL 2 KABUPATEN WONOSOBO - Anggi Arizty Pratiwi; Farihah Indriani; Nazilla Nugraheni; Suharti (Jurnal Ilmiah Kesehatan, 2025)
Comprehensive midwifery care is a continuous service for pregnant women, childbirth,newborns, neonates, postpartum and family planning. The aim is to describe comprehensivemidwifery care for Mrs. S, 24 years old with mild anemia in the third trimester of pregnancyat the Kepil 2 Community Health Center, Wonosobo Regency from February 27, 2025 – April25, 2025. The research method uses a case study approach with the One Student One Client(OSOC) model and SOAP documentation. The results of care show an improvement in themother’s condition during pregnancy, labor proceeded normally with the management ofshoulder dystocia and umbilical cord loosening, the baby was born healthy, the neonate wasfound to have problems with physiological weight loss, the postpartum period wasphysiological, and the mother chose the 3-monthly injection contraceptive method.Comprehensive and standardized midwifery services can improve the quality of maternal andinfant health and reduce the risk of complications